IMPLEMENTATION OF SCHOOL BOARDING SERVICE QUALITY ON ACADEMIC ACHIEVEMENT AT ISLAMIC JUNIOR HIGH SCHOOLS IN RIAU ISLANDS PROVINCE - Sofwatillah Sofwatillah; Kasful Anwar; Mahmud MY; Asrulla (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Education is a fundamental pillar in shaping a superior and character-driven generation, with boarding schools providing a unique 24-hour integrated learning and living environment that acts in loco parentis. This study examines the implementation of service quality in Islamic boarding schools in the Riau Islands Province and its influence on academic achievement, focusing on SMPIT Assakinah Tanjung Pinang, SMPS Al-Himmah Karimun, and SMP BP Tahfidz Attaubah Batam. Service quality in this context is defined as a student-centered paradigm that integrates academic, pastoral, and social dimensions. Drawing on perspectives from Crosby, Sallis, and Brewster, quality is measured by responsiveness to needs, continuous improvement, and the integration of academic rigor, pastoral care, and co-curricular enrichment. Academic achievement, as described by Bloom, is shaped by cognitive, affective, and environmental factors, where the structured environment of boarding schools can maximize outcomes. This research employed a qualitative case study approach with data gathered through observation, interviews, and documentation, analyzed using an interactive model. Findings reveal that service quality is implemented through four stages: (1) conceptualization with a vision integrating national and diniyah curricula; (2) implementation involving active learning, dormitory services, extracurricular programs, and Islamic character building; (3) improvement via SWOT-based evaluation, facility upgrades, teacher development, and digitalization; and (4) continuous evaluation for relevance and effectiveness. The study concludes that comprehensive, integrated service quality is a decisive factor for success in boarding schools. Effective service quality fosters both academic achievement and the development of religious, independent, and morally sound students. By applying Total Quality Management principles, Islamic boarding schools can establish an optimal educational ecosystem, producing a superior and globally competitive generation rooted in Islamic values.